Analisis Hukum Islam Terhadap Perkawinan Dengan Penderita Gangguan Jiwa Atau Bipolar - Arinda, Syifa; Dinda Seplinar Batubara; Keisyah Yuvi Amanda; Latif, Abdul; M. Rifky Abdillah (Yayasan Dar Arrisyah Indonesia, 2024)
Marriage in Islam is a sacred bond that binds two individuals in a family relationship. However, challenges arise when one partner suffers from bipolar disorder, a mental condition characterized by extreme mood swings. This research aims to analyze Islamic law regarding marriage for bipolar sufferers, examine the views of ulama, and understand how this condition affects the validity and sustainability of marriage. The research method used is qualitative with a descriptive-analytical approach to fiqh literature, ulama fatwas, and case studies. The research results show that in Islam, transparency and honesty before marriage are highly prioritized, including disclosure of mental health conditions. Scholars agree that bipolar sufferers still have the right to marry, but the obligation to provide information to their prospective partner is important so that both parties can make the right decision.